Pro-Inflammatory Cytokines Predict the Response of Cancer Treatment - Mir, Umar Farooq; Jha, Deepak Kumar; Chatterjee, Sandipan (Indian Journal of Pharmaceutical Education and Research, 2025)
The immune condition has an important effect on cancer growth and progression at both the systemic and neoplastic microenvironment levels. Immune modulation or activation has clinical significance for prognostic and diagnostic purposes. Cytokines are signalling proteins that allow communication between cells and are essential for a functioning immune system. Innate and adaptive immune cells, as well as non-immune cells and tissues, communicate via cytokines. Understanding the body's reaction to illness and therapies can be aided by keeping track of the levels of cytokines in the blood and other body fluids. According to reports, a few studies have shown the benefit of routinely checking cytokine levels in tumors. The main objective of the review is to understand the disease and treatment to help evolving immune environment. Along with blood observations, cytokines such as Interleukin-6, Interleukin-8, Interleukin-10, Interferon-Gamma, Tumor Necrosis Factor-Alpha and Transforming Growth Factor-Beta can be employed as predictive/prognostic biomarkers to assist comprehend the changing immunological milieu throughout illness progression and treatment. This study focuses on recent advances in cancer treatment like, proinflammatory cytokine-related processes, diagnostic markers and clinical applications.
Keywords: Cancer; Cytokines; Immune System; Tumor Markers.